The Role of CEO Characteristics in ESG Risk Assessment: Empirical Evidence from the ESGQ 45 IDX KEHATI Index - Ade Yuniati (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
This research examines the characteristics of CEOs, such as age, educational background, and tenure, toward ESG risk assessment. These characteristics influence strategic decisions to reduce ESG risk in order to achieve a green economy and sustainable development. This research used purposively selected sample of 34 companies which listed on the ESGQ 45 IDX KEHATI index based on data from 2024. Data analysis used multiple regression analysis. This research finds that CEOs with a business education background are able to reduce ESG risk. This educational background provides the skills needed for better risk analysis, including identifying potential ESG issues. However, the age and tenure of the CEOs have no effect on ESG risk. Age and tenure of the CEOs are attributes that do not reflect strategic capacity in reducing ESG risk.